Towards Green Transportation Practices Using a Buyer/Supplier Perspective: A Systematic Literature Review - Gisèle Mendy Bilek; Richard Calvi; Daniel Erhel; Youcef Mechouar (Logistics)
Background: The role of individual supply chain actors in carbon emissions reduction (CER) is well-documented. However, it is critical to identify the conditions required to develop a systemic approach for encouraging these actors to share their visions and align their environmental strategy for CER. This study aims to identify the determinants (motivations, pressures, and incentives) and modalities (practices conducting greening transportation from shippers and logistics service providers (LSP) point of view) necessary for a better environmental alignment between actors for a CER initiative. Methods: We base our argument on a systemic literature review that points out 28 articles written in the period between 2010 and 2023 and fully aligned with the scope of our analysis. Results: The originality of our approach is that we focus on the interplay between shippers and LSPs to better understand the dynamics of green transportation practices. Conclusions: This paper invites researchers to adopt a dyadic approach to the phenomenon in order to better understand how the CER willingness is effectively diffused in the business interactions of shippers and LSP.